2020
DOI: 10.1111/1471-0528.16068
|View full text |Cite
|
Sign up to set email alerts
|

The cost‐effectiveness of progesterone in preventing miscarriages in women with early pregnancy bleeding: an economic evaluation based on the PRISM trial

Abstract: Objectives To assess the cost‐effectiveness of progesterone compared with placebo in preventing pregnancy loss in women with early pregnancy vaginal bleeding. Design Economic evaluation alongside a large multi‐centre randomised placebo‐controlled trial. Setting Forty‐eight UK NHS early pregnancy units. Population Four thousand one hundred and fifty‐three women aged 16–39 years with bleeding in early pregnancy and ultrasound evidence of an intrauterine sac. Methods An incremental cost‐effectiveness analysis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…To conclude, Coomarasamy et al demonstrated, in a subgroup analyses of the PRISM and PROMISE trials, that in women presenting with dual risk factors of early pregnancy bleeding and a history of one or more previous miscarriages, progesterone has a beneficial role by increasing LBR by 5%, whereas women with at least 3 previous miscarriages benefit the most by progesterone supplementation [69 ▪ ]. A Cochrane review suggested that progesterone may improve LBRs [70], however, the cost efficiency of progesterone in the treatment of RM has been questioned [71 ▪ ,72 ▪▪ ].…”
Section: Unexplained Recurrent Miscarriagesmentioning
confidence: 99%
“…To conclude, Coomarasamy et al demonstrated, in a subgroup analyses of the PRISM and PROMISE trials, that in women presenting with dual risk factors of early pregnancy bleeding and a history of one or more previous miscarriages, progesterone has a beneficial role by increasing LBR by 5%, whereas women with at least 3 previous miscarriages benefit the most by progesterone supplementation [69 ▪ ]. A Cochrane review suggested that progesterone may improve LBRs [70], however, the cost efficiency of progesterone in the treatment of RM has been questioned [71 ▪ ,72 ▪▪ ].…”
Section: Unexplained Recurrent Miscarriagesmentioning
confidence: 99%
“…Reproduced from Okeke Ogwulu et al 52 During the antenatal period, women allocated to the progesterone arm had, on average, a higher frequency of antenatal and DAU visits but a smaller number of emergency room visits and hospital admissions than women in the placebo arm. During the postnatal period, women in the progesterone arm utilised similar services more than those in the placebo arm except for emergency hospital visits, which were the same for both arms.…”
Section: Resource Use and Costsmentioning
confidence: 99%
“…Cost-effectiveness plane for the primary analysis using hospital-related costs for the participants. Reproduced from Okeke Ogwulu et al52 © 2020 The Authors. BJOG: An International Journal of Obstetrics and Gynaecology published by John Wiley & Sons Ltd on behalf of Royal College of Obstetricians and Gynaecologists.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[10,11,15] About 30-50% [8,16,17] of VB-affected deliveries end in a miscarriage. [18][19][20] The long-term risk of cancer in women with a pregnancy complicated by vaginal bleeding within 20 gestational weeks is unknown. A previous Danish study showed that VB in pregnancy is not a marker of occult cancer.…”
Section: Introductionmentioning
confidence: 99%